Anticancerous efect of Typhonium flagelliforme on human T4-lymphoblastoid cell line CEM-ss - Mohan, Syam; Abdul, Ahmad Bustamam; Abdelwahab, Siddiq Ibrahim; Al-Zubairi, Adel Sharaf; Sukari, Mohd Aspollah (Academic Journals, 2008)
Typhonium flagelliforme (Lodd.) Blume, commonly known as rodent tuber in Malaysia, is one of the widely used alternative medicines in cancer therapy by South East Asian population. Intake of this plant is common among patients with malignancies especially Leukaemia, breast and cervical cancer; however no data available regarding the possible direct effect of T flagelliforme in these cancers. The purpose of the present study was to investigate the potential m vitro cytotoxic effect of leaves and tubers of T. flagelliforme extracts against human T4-lymphoblastoid cell line CEM-ss. Among the 8 extracts Dichloromethane and Ethyl acetate extracts of T. flagelliforme demonstrated significant anti proliferative effect with a marked level for both leaves (10.8 and 5.8 Î¼g mL-1) and tuber (6.5 and 8.2 Î¼g mL-1), against CEM-ss cells. Considering all the results collectively T. flagelliforme appears to be a promising plant demonstrating anti cancer activity, that requires further investigation.